The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1186/s12883-023-03359-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of virtual reality combined with repetitive transcranial magnetic stimulation on musculoskeletal pain and motor development in children with spastic cerebral palsy: a protocol for a randomized controlled clinical trial

Xin Li,
Zefan Huang,
Tijiang Lu
et al.

Abstract: Purpose This trial aims to investigate the efficacy and safety of virtual reality (VR) combined with repetitive transcranial magnetic stimulation (rTMS) for improving musculoskeletal pain and motor development in children with unilateral spastic cerebral palsy (CP). Methods This study protocol is for a randomized controlled trial consisting of 2 treatment sessions (3 days/week for 4 weeks in each session, with a 1-week interval between sessions). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Analyzing the relationships between the control parameters and key biomechanical indicators and achieving standardized comparisons between different control strategies may better guide the future technological development of exoskeleton robot-assisted walking rehabilitation. Recent clinical trials have also revealed that treatment methods developed in neurorehabilitation have been widely studied in CP research, such as transcranial magnetic stimulation ( 48 ), virtual reality technology ( 48 ), whole-body vibration ( 49 ), wearable exoskeletons, and stem cell transplantation ( 45 , 50 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the relationships between the control parameters and key biomechanical indicators and achieving standardized comparisons between different control strategies may better guide the future technological development of exoskeleton robot-assisted walking rehabilitation. Recent clinical trials have also revealed that treatment methods developed in neurorehabilitation have been widely studied in CP research, such as transcranial magnetic stimulation ( 48 ), virtual reality technology ( 48 ), whole-body vibration ( 49 ), wearable exoskeletons, and stem cell transplantation ( 45 , 50 52 ).…”
Section: Discussionmentioning
confidence: 99%